2017
DOI: 10.1083/jcb.201705130
|View full text |Cite
|
Sign up to set email alerts
|

Srf controls satellite cell fusion through the maintenance of actin architecture

Abstract: This work describes a crucial role for the transcription factor Srf and F-actin scaffold to drive muscle stem cell fusion in vitro and in vivo and provides evidence of how actin cytoskeleton architecture affects myoblast fusion in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 52 publications
3
70
0
Order By: Relevance
“…2). Our evidence implies that these filaments are lamellipodia resulting from actin polymerization, causing finger-like actinbased protrusions at the muscle cells' fusion sites [44,60,62]. This reorganization of actin cytoskeletal structures, as a result of actin or actin-regulatory protein phosphorylation, is mediated by the PI3K/Akt-signal-transduction pathway [63,64].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…2). Our evidence implies that these filaments are lamellipodia resulting from actin polymerization, causing finger-like actinbased protrusions at the muscle cells' fusion sites [44,60,62]. This reorganization of actin cytoskeletal structures, as a result of actin or actin-regulatory protein phosphorylation, is mediated by the PI3K/Akt-signal-transduction pathway [63,64].…”
Section: Discussionmentioning
confidence: 70%
“…One of the reasons for this phenomenon might be impairment in the myotubes' ability to form actin filaments ( Fig. 2), which are crucial for cell movement and the cell-cell fusion process [44,45,[58][59][60]. It has also been demonstrated that under local membrane-injury protocols, dysferlin recruitment to the injury site is impaired if the formation of actin filament protrusions is inhibited [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3H; Fig. S7A; Movie 5,6). However, upon GTP addition, the disassembly of Shi rings resulted in the exposure of actin bundle sides, thus allowing robust branched actin polymerization from their sides ( Fig.…”
Section: Dynamin Bundles Actin Filaments In Vivomentioning
confidence: 95%